2019
DOI: 10.1104/pp.19.00752
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Control of Root System Architecture between Zea mays and Sorghum bicolor

Abstract: Determining the genetic control of root system architecture (RSA) in plants via large-scale genome-wide association study (GWAS) requires high-throughput pipelines for root phenotyping. We developed Core Root Excavation using Compressed-air (CREAMD), a high-throughput pipeline for the cleaning of field-grown roots, and Core Root Feature Extraction (COFE), a semiautomated pipeline for the extraction of RSA traits from images. CREAMD-COFE was applied to diversity panels of maize (Zea mays) and sorghum (Sorghum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 106 publications
(130 reference statements)
0
58
0
Order By: Relevance
“…Among other methods, mapping root intersection in a soil profile by the trench profile method was identified to be more efficient and feasible to provide information on roots distribution [32,35,36]. Despite tremendous progress performed in genetic characterization of root development [37], root system architecture phenotyping remains challenging particularly in field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among other methods, mapping root intersection in a soil profile by the trench profile method was identified to be more efficient and feasible to provide information on roots distribution [32,35,36]. Despite tremendous progress performed in genetic characterization of root development [37], root system architecture phenotyping remains challenging particularly in field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that these root traits shared a similar regulation mechanism. We also compared our results with the other root GWAS studies both in hydroponics and field, but ZmCKX5 was not picked up by previous GWAS [ 18 , 19 ]. This indicates the complexity of the root regulation mechanism to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Association analysis is an effective way to analyze the genetic mechanism of complex traits. This research option has been applied to investigate root development in maize [ 18 , 19 , 20 , 21 ]. To investigate the natural variation of ZmCKX genes, single-nucleotide polymorphism (SNP) in ten CKX genes were filtered from a genotyping-by-sequencing (GBS) dataset in 285 inbred lines.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found an association between drought tolerance and metaxylem vessel number (de Souza et al, 2013;Klein et al, 2020) or metaxylem vessel area (Richards and Passioura, 1989;Abd Allah et al, avoid false positives and isolate the true loci with significant causal effects on phenotype. One method to increase robustness of an associative mapping study is by conducting a comparative multispecies GWAS, which has the potential to enhance our understanding of shared genetic architectures among species (Chen et al, 2016;Zheng et al, 2020). Although maize and rice are different in many respects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these differences, shared genetic machinery underlying xylem development is likely, as is the case for example for the cellulose synthase A (CesA) gene family, which is present in all seed plants (Richmond and Somerville, 2000). Furthermore, comparisons between maize and closely related species have found shared genetic architecture influencing sorghum ( Sorghum bicolor ) root architecture (Zheng et al, 2020) and rice ( Oryza sativa ) grain development (Chen et al, 2016). These studies suggest there is a high likelihood that the genetic machinery regulating other developmental processes, like xylem development, may be conserved within monocots.…”
Section: Introductionmentioning
confidence: 99%